Relationship Between Innovative Work Behavior, Competitive Advantage and Business Performance - Ahmad Firdaus; Sakinah Sakinah (Universitas Batanghari, 2022)
The aims of this study is to see how the influence of innovative work behavior on business performance in SMEs, while the mediating variable is competitive advantage. Innovative work behavior is the basis for developing excellence which will impact business performance. The sample in this study were 111 SMEs in Jambi province, especially those that had been established for more than 5 years. the data used is primary data taken through questionnaires distributed to 111 SMEs managers, and processed with verification analysis techniques using structural equation modeling.